17.0k views
1 vote
What is the solution to the open sentence?  4y – 3 = y + 6   A. 1   B. 2   C. 3   D. 9

User Ramar
by
6.2k points

2 Answers

2 votes
4y - 3 = y + 6
Add 3 to both sides
4y = y + 9
Subtract y from both sides
3y = 9
Divide both sides by 3
y= 3
User Sathish Kumar VG
by
6.8k points
2 votes

Answer:

Option A - 1

Explanation:

Given : Expression
4y-3=y+6

To find : What is the solution to the open sentence?

Solution :

Step 1 - Write the expression,


4y-3=y+6

Step 2 - Take like terms together,


4y-y=6-3

Step 3 - Solve the addition and subtraction,


3y=3

Step 4 - Divide by 3 both side,


(3y)/(3)=(3)/(3)


y=1

Therefore, Option A is correct.

User HenryChuang
by
5.8k points